Thermoluminescence of ï§-irradiated SrAl2O4:Dy - Choubey, Anil Kumar; Brahme, Nameeta; Bisen, D P; Dhoble, S J (Recent Research in Science and Technology, 2012)
Thermoluminescence (TL) properties of ï§-irradiated Strontium Aluminate doped with Dy (10% molar concentration) was studied. The phosphor was synthesized by combustion method using urea as a reducer at initiating temperature of 600oC. Dy doped SrAl2O4 is a good dosimeter having linear response upto 2360 Gy of ï§-dose. The kinetic parameter have been calculated using Chen’s glow curve method.